Using free webmail gmail, hotmail, yahoo mail - Vaccaro, Guy; Safari eBooks ([Place of publication not identified] : Infinite Skills, 2010)
"In this computer based training course, expert author Guy Vaccaro takes a look at the three most popular free Webmail services, Yahoo! Mail, Google Gmail and Microsoft Hotmail/Windows Live. With Guy, you will explore the three top free email services on the internet, learning how to signup for them, create, send and manage your emails, as well as the additional services each offer, Calendars and Contacts. You will tour the interface, and become comfortable with the idiosyncrasies of each of the programs. This video based training course allows you to follow the author through teaching you each subject, in an easy to learn manner. By the completion of this video tutorial, you will be able to choose which service best suits your needs, and be familiar with the interface and use of the features of the free email service that you choose to use!"--Resource description page.
Title and publication info taken from resource description page (viewed February 12, 2015).
Speaker, Guy Vaccaro.
Keywords: Electronic mail systems; Electronic mail messages; Gmail (Electronic resource); Electronic books